8 Prevalence and Significance of Early Repolarisation Pattern ECG in Patients with Syncope. (31st May 2014) - Frontera, Antonio; Carpenter, Alexander; Ahmed, Nauman; Fasiolo, Matteo; Sathianarayana, N; Diab, Ihab; Cripps, Timothy; Thomas, Glyn; Duncan, Edward
Abstract : Introduction: Historically an early repolarization (ER) pattern ECG was considered a benign finding, but since 2008 it has been associated with an increased risk of sudden cardiac death. There is now active debate on how to recognise pathological ER. The prevalence of ER in the general population is reported to be up to 13%. Case reports have described syncope preceding sudden cardiac death in patients with ER. There are no studies published in the literature describing the incidence of ER in patients with syncope or longterm outcomes in this group. We describe the prevalence of ER in patients investigated for syncope at our institution. Methods: We searched retrospectively for patients over 18 years of age who underwent a loop recorder (LR) implant for syncopal episodes from January 2010 to March 2013. Clinical data for demographics, comorbidities and device data were collected from the procedural record, medical notes and follow-up notes. LR checks were performed every 3 months in our pacing clinic or every time the patient activated the recorder. All ECGs were examined by two blinded electrophysiologists. An ER pattern was identified according to HRS criteria (J-point elevation ≥ 1 mm in ≥2 contiguous inferior and/or lateral leads of a standard 12-lead ECG). All follow up EGMs were examined for ventricular arrhythmias. Results: Our LR population consists of 200 patients, (103 male) with a median age of 61.9 years (range 18–88). Median follow-up was 15.4 months (range 6–33). 154 of them had an LR implanted to investigate their syncope. Of these 154 patients, 94 (61%) had hypertension, 43 (27.9%) hypercholesterolemia, 16 (10.3%) diabetes, 33 (21.4%) were smokers, 3 were sportsmen (2%). One patient had a family history of sudden cardiac death. 135 patients (87.6%) had a structurally normal heart (EF > 50%). 28 patients (18.1%) had ischaemic disease. ER pattern was identified in 12 patients (7.8 %), 8 were male with a median age of 35.8 years. In 5 patients the ER pattern was localised in lateral leads (lead I, avL, V5, V6), in 5 the ER pattern was present in inferior leads (lead II, lead III, avF), 2 were in infero-lateral leads. J point elevation was >2 mm only in 6 patients, (5 male). No documented ventricular arrhythmias were seen during follow up of the patients with ER. We recorded only 1 death due to respiratory arrest. Loop interrogation excluded any arrhythmia. Conclusion: In our study we identified ER in the ECG of 7.8% of patients who had a LR implanted for syncope. This finding is comparable to the incidence of ER pattern reported in the general population. We didn't record any ventricular arrhythmias among this population. Our early data suggests that ER among patients with syncope is a fairly benign pattern. Other markers of risk will be needed to identify those at risk of sudden death amongst this population.